2000
DOI: 10.2307/1468131
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir–river linkages: Lake Powell and the Colorado River, Arizona

Abstract: The effect of lotic-lentic interactions on the phytobenthic community was studied in the Colorado River below Glen Canyon Dam (GCD), Arizona. Major compositional changes in river phytobenthos occurred following high snowmelt inflows that filled the Lake Powell reservoir and resulted in high, steady discharges from GCD. Cladophora glomerata, the previously dominant alga, was partly displaced by a mixed mucilaginous phytobenthic assemblage consisting of miscellaneous algae, macrophytes, and bryophytes (MAMB). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Moss cover on upper stone surfaces declines inversely with the stability of the substratum, which among other factors, also depends on stone size (McAucliffe, 1983). The experimental flood below the Glenn Canyon Dam (Colorado River) showed that bryophytes were more susceptible to high flow than the filamentous macroalga Cladophora glomerata (Benenati et al, 2000). The low frequency of high flow events in the Spöl before 1999 favored moss growth also on relatively small rocks, which were highly stable under the residual flows, but were moved or subject to abrasion by moving bed sediment during the experimental floods.…”
Section: Periphytonmentioning
confidence: 99%
“…Moss cover on upper stone surfaces declines inversely with the stability of the substratum, which among other factors, also depends on stone size (McAucliffe, 1983). The experimental flood below the Glenn Canyon Dam (Colorado River) showed that bryophytes were more susceptible to high flow than the filamentous macroalga Cladophora glomerata (Benenati et al, 2000). The low frequency of high flow events in the Spöl before 1999 favored moss growth also on relatively small rocks, which were highly stable under the residual flows, but were moved or subject to abrasion by moving bed sediment during the experimental floods.…”
Section: Periphytonmentioning
confidence: 99%
“…Basu and Pick [] observed rotifers to be more populous in lake environments and Benenati et al . [] expected declines in Cladocera with increased lotic velocity. Hoffsten and Malmqvist [] used predetermined lentic and lotic taxa assemblages to predict the sources of species measured in a glaciofluvial spring.…”
Section: Introductionmentioning
confidence: 99%
“…The reservoir shows a consistent seasonal variation, with increases of around 10-20 km 3 during the first five months, and decreases over the last seven months of the year (Figure 6b). Moreover, the lake gained at least 45 km 3 of water from 1996 to 1999. , Lake Powell is the largest lake in the U.S. by water surface area (Barnett and Pierce, 2008;Benenati et al, 2000). Its maximum capacity of 33.3 km 3 is slightly less than that of Lake Mead (Benenati et al, 2000;Holdren and Turner, 2010).…”
Section: Volumetric Resultsmentioning
confidence: 99%
“…Moreover, the lake gained at least 45 km 3 of water from 1996 to 1999. , Lake Powell is the largest lake in the U.S. by water surface area (Barnett and Pierce, 2008;Benenati et al, 2000). Its maximum capacity of 33.3 km 3 is slightly less than that of Lake Mead (Benenati et al, 2000;Holdren and Turner, 2010). The lake showed two periods of maximum capacity during 1984-1988 and 1995-2000 …”
Section: Volumetric Resultsmentioning
confidence: 99%